A novel missense ALMS1 variant causes aberrant splicing identified in a cohort of patients with Alström syndrome - Shi, Jie; Xu, Ke; Zhang, Xin; Xie, Yue; Chang, Haoyu; Li, Yang (Frontiers in Genetics, 2023)
Purpose: Alström syndrome (AS) is a rare autosomal recessive disorder caused by variants of ALMS1. The objectives of this study were to describe the clinical and genetic characteristics of 19 Chinese patients with biallelic variants in ALMS1. Methods: We recruited 19 probands with biallelic disease-causing ALMS1 variants. All patients underwent ophthalmic and systematic evaluations and comprehensive molecular genetic analysis. Reverse transcriptase-polymerase chain reaction (RT-PCR) assays were performed to observe the effect of a novel missense variant on ALMS1 pre-mRNA splicing. Results: We identified 33 causative variants in ALMS1, including 15 frameshift small indels, 14 non-sense variants, two gross deletions, one splicing variant, and one missense variant. RT-PCR showed that the missense variant c.9542G>A (p.R3181Q) altered pre-mRNA splicing to generate a truncated protein p. (Ser3082Asnfs*6). Retinal dystrophy (RD) was noted in all the patients, followed by metabolism disturbance (obesity or acanthosis nigricans) in 66.7% and hearing impairment in 61.1% of the patients. Patient systemic symptom numbers and their age at evaluation showed a significant positive correlation, and BCVA and age at the last examination showed a moderate correlation. All patients exhibited early-onset RD and severe visual impairment. The exception was one patient carrying homozygous p. R3181Q, who showed a mild visual defect and atypical retinal phenotype. Conclusion: Our findings expand the pathogenic variant spectrum of ALMS1 and provide the first verification of a novel missense variant caused AS by aberrant pre-mRNA splicing. Patients with AS might demonstrate varied clinical spectra; therefore, genetic analysis is vital for the early and accurate diagnosis of patients with atypical AS.